2018
DOI: 10.18287/2412-6179-2017-42-5-877-884
|View full text |Cite
|
Sign up to set email alerts
|

Experimental determination of soil moisture on hyperspectral images

Abstract: The possibility of humidity determination based on the use of spectral distributions in the wavelength range of up to 1 µm is analyzed. We discuss the use of an imaging hyperspectrometer for precision farming. A field experiment to determine the soil moisture index under the vegetation cover is described. A procedure of precise calibration of the hyperspectrometer based on the use of a tunable laser is described. We show the possibility of the practical determination of humidity based on the use of spectra in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…The experiment will allow us to check the working element under different conditions to find out the most suitable parameters for our working element for a specific channel [6][7][8][9][10] The screw-type element of the plant residue cleaner has several parameters. To simplify the work we will distinguish three main ones: T -the flight screw pitch cm, Ds -diameter of the screw cm, n -speed, r.p.m.…”
Section: Methodsmentioning
confidence: 99%
“…The experiment will allow us to check the working element under different conditions to find out the most suitable parameters for our working element for a specific channel [6][7][8][9][10] The screw-type element of the plant residue cleaner has several parameters. To simplify the work we will distinguish three main ones: T -the flight screw pitch cm, Ds -diameter of the screw cm, n -speed, r.p.m.…”
Section: Methodsmentioning
confidence: 99%
“…First, we insist on the complete preservation of the reference HSI pixel signatures, regardless of the number of channels that are necessary for the current classification in a particular application (perhaps with the exception of completely noisy channels). This will allow us to build a classification, which is not so much dependent on the conditions of a specific task and a specific HSI, but is reusable and is supported by reference (standard) signatures, which were confirmed in field tests, as in [3], [4], [6][7][8][9][10].…”
Section: Methods Of Analysis and Markup Of Hsi Objectsmentioning
confidence: 99%
“…In [8], 2018, the use of imaging hyperspectrometers for precision farming in a field experiment to determine the humidity index of soil covered with vegetation is considered. It is shown that the humidity index at each point of the hyperspectral image, where greens are present, is determined by the ratio of I 0,9 to I 0.97 , where I 0.9 is the spectral brightness at a wavelength of 0.9 μm, and I 0.97 is at a wavelength of 0, 97 microns.…”
Section: Review Of Publications On the Research Topicmentioning
confidence: 99%
“…Information and analytical analysis of special literature on practice of reclamation, both in Russia and abroad indicates the presence of various empirical dependencies for determining crop evapotranspiration, which are the critical factor in the expenditure part of the water balance equation for an irrigated field. The amount of evapotranspiration depends on a significant number of factors, both natural, including soil water-physical and chemical properties, actual hydrometeorological conditions, soil moisture, hydrological characteristics of irrigated areas of the corresponding irrigation zones, and the physiological properties of plants, progressive technologies of their cultivation, taking into account reclamation technologies [1][2][3][4]. Scientific and technological progress in reclamation science development justifies the urgent need in application of a new methodological approach to the development and implementation of processes for resource-saving water use, including agricultural crops irrigation.…”
Section: Introductionmentioning
confidence: 99%